ANALISIS KERJASAMA PEMERINTAH PROVINSI JAWA TENGAH DAN PERUM PERHUTANI TERKAIT PERUBAHAN PERUNTUKAN PENGGUNAAN KAWASAN HUTAN PRODUKSI PENGGARON MENJADI JATENG PARK - Wisnuputro, Rois Satrio; ., Yuwanto; Astrika, Lusia (Journal of Politic and Government Studies, 2017)
This research aims to examine the cooperation of the Provincial Government of Jawa Tengah with Perum Perhutani in order to develope a new tourism destination of Central Java Park where located in Penggaron Production Forest, Kabupaten Semarang. The cooperation is carried out in the framework of the Provincial Government of Jawa Tengah plans to find alternative tourist destinations in Jawa Tengah. In addition, the purpose of Central Java Park development is to increase the local revenue (PAD) of Jawa Tengah province. To that end, Provincial Government of Jawa Tengah appointed Perum Perhutani as Penggaron Forest land owner to cooperate in building Central Java Park. This research analyzes the cooperation process conducted by both parties starting from the idea to the implementation, knowing the supporting and inhibiting factors from the cooperation of both parties in the development of Central Java Park. Researchers chose related parties such as Central Java Provincial Government and Perum Perhutani KPH Semarang as a case study study.The method used in this research uses a qualitative approach with descriptive method. In obtaining the data, the researcher uses interview method with the research informant is the Bureau of Infrastructure and Natural Resources of Central Java Province, Perum Perhutani Unity of Semarang Forest Stakeholders and other Parties involved in the cooperation. Researchers also use secondary data derived from relevant Regional Regulations as well as other literary sources such as books and journals.The results showed that the process of cooperation between the two sides is still not good in terms of communication. This is evidenced by the length of time required in the assessment of cooperation and the division of development responsibilities Central Java Park. From it shows the cooperation is not running effectively. Therefore, both parties must be more firm and committed in implementing such cooperation so that the development of Central Java Park will be more quickly implemented.Â Keywords: Public Private Partnerships, New Company, Beauty Contest